Social venture acquisition, in the form of strategic alliance building and earnings generation as a means of achieving scalability of social enterprises - Bukula, Sanelisiwe (My University, 2021)
Social problems continue to persist and large enterprises, together with social enterprises, can play a role incoming up with innovative solutions to these problems. Social enterprises have the potential to implement business-like approaches to expand, scale up and match the needs of the problem, however, they fail and that makes scaling one of the most important phenomenon to study as it is least understood currently. Extending from existing, mostly conceptual research, the study sought to add empirical evidence on a scaling framework that explored only two variables of the SCALERS model, the earning generation and strategic alliance capabilities of social enterprises and their relationship with scaling of the enterprise. The research purpose was to add to the still limited theory on the field of scaling of social enterprises to enable the social entrepreneurial ventures to strategically move their enterprises beyond the start-up phase and scale for greater impact. The study adopted a cross-sectional quantitative research, utilising an on-line self-administered survey, to collect data with random non-probability sampling of social entrepreneurs in South Africa. Findings suggest that strategic alliance building on its own does not have a significantly positive relationship with scaling and earnings generation is positively and significantly related to the scaling of the social enterprise. Findings also suggest more work on the measurement instrument and the validity of constructs in new geographical contexts is needed. Earnings generation which can be leveraged off CSR investments and other related investments can be prioritised by the social entrepreneur when deciding to scale the social enterprise. More value can be derived from such studies to enable strategic decision-making and assumptions derived from empirical research
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in Entrepreneurship and New Venture Creation), 2021
Keywords: Social entrepreneurship; corporate social responsibility; financial sustainability; geographic context; SDG-8: Decent work and economic growth